Influences of the Cu Substitution at Hg Site in Hg1 - xCuxBa2Ca2Cu3O8+δ Superconductors - Abbas, M. M. (Iraqi Journal of Physics, 2008)
The influences of the Cu substitution at Hg site in the HgOd layer, upon the microstructure, Tc and oxygen content of Hg-1223 have been investigated. High temperature superconductor with a nominal composition Hg1-xCuxBa2Ca2Cu3O8 + δ for Cu ( 0 £ x £ 0.5) have been prepared by the two-steps solid state reaction method under optimum conditions. XRD showed a tetragonal structure with a high ratio of Hg-1223 superconductor phase. Tc enhancement has been determined with the Cu concentration was is found to be Tc = 153 K for x = 0.3, while the oxygen content observed variously with Cu concentration. Hg1-xCuxBa2Ca2Cu3O8+δ structure, oxygen content and Tc behavior have been discussed.